2001
DOI: 10.1007/s004200000200
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of scientific researchers I. Characteristics of job stress among scientific researchers working at a research park in Japan

Abstract: In order to clarify the characteristics of job stress in scientific researchers, a self-administered questionnaire survey for 16,330 workers was carried out at Tsukuba Research Park City, Japan. The data of 7,063 (43%) workers aged 20-59 years old were analyzed, and the characteristics of job stress in 3,290 scientific researchers were compared with those of 1,799 technicians and 1,849 clerks. The researchers perceived higher quantitative and qualitative workload, greater job control (job decision latitude), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
5
5
0
1
Order By: Relevance
“…According to other studies from different cultural backgrounds and professions (Godin and Kittel 2004;Godin et al 2005;Kageyama et al 2001;Larisch et al 2003;Li et al 2006;Niedhammer et al 2004;Pikhart et al 2004;Preckel et al 2005;Rockenbauch et al 2006), we also found a strong relationship between stress at work measured by the ERI model and self-reported health. It is a matter of concern that ongoing stress at work leads to serious physical and mental problems, especially symptoms of anxiety disorder and depression and low satisfaction with life in young physicians.…”
Section: Work Stress and Self-reported Healthsupporting
confidence: 85%
“…According to other studies from different cultural backgrounds and professions (Godin and Kittel 2004;Godin et al 2005;Kageyama et al 2001;Larisch et al 2003;Li et al 2006;Niedhammer et al 2004;Pikhart et al 2004;Preckel et al 2005;Rockenbauch et al 2006), we also found a strong relationship between stress at work measured by the ERI model and self-reported health. It is a matter of concern that ongoing stress at work leads to serious physical and mental problems, especially symptoms of anxiety disorder and depression and low satisfaction with life in young physicians.…”
Section: Work Stress and Self-reported Healthsupporting
confidence: 85%
“…As expected from the above job environment, the GHQ scores and the CES-D scores in our subjects were high, showing that they are at poor mental health status compared with the general workers 22,23,28,30) . This agrees with many previous studies on Japanese hospital nurses [33][34][35] .…”
Section: Discussionsupporting
confidence: 72%
“…The latter includes the scales for severity of patients' illness and difficulty in patient-nurse relationships, which are proper stressors to hospital nurses. The reliability and validity of these scales are previously reported 16,[22][23][24] . The number of recent major life events was counted using a previously reported method 18) .…”
Section: Methodsmentioning
confidence: 99%
“…A study in radiographers (Rutter and Lovegrove 2008) reported superintendents had significantly greater stress than junior staff and social support could reduce the effect of role conflict on perceived stress. According to other studies (Kageyama et al 2001;Preckel et al 2005), we found a strong relationship between occupational stress and health function. Some studies also evaluated the coping strategies of occupational stress on doctors (Kinzl et al 2007;Wallace and Lemaire 2007).…”
Section: Introductionsupporting
confidence: 53%